Early Algebra: The Levels of 3th, 4th and 5th Grade Students' Generalisations of Functional Relationship - Dilek Tanışlı; Handegül Türkmen (Anı Publishing, 2019)
The purpose of this study is to determine the students' levels of generalisation of functional relationships in third, fourth and fifth grade. The design of the study was a basic qualitative research study. Participants were 116 students; 45 from the third grade, 36 from the fourth grade and 35 from the fifth grade from a middle school. The data were collected with the help of open-ended questions. Thematic analysis was used to analyze the data. In this context, the levels of functional thinking previously developed in the literature have been taken into consideration and some of these levels have been used in this research and at the same time some levels of lower levels have been formed. It has been seen that most students at all grade levels have many indications of functional thinking in general but some students have more difficulty in generalizing and representing the general rule y=mx+n. This result shows that the functional thinking of the students in the early algebra period can be improved. Therefore, it is necessary to increase the activities that develop functional thinking in curriculum and textbooks at an earlier age.